Omphalophlebitis in a Calf - Treatment with Umbilical Vein Marsupialization - Kátia Rocha Tonhá,; Dyana Ribeiro dos Santos,; Nathasha Freitas Marcelino,; Wanessa Patrícia Rodrigues da Silva,; Leandro Guimarães Franco,; Paulo José Bastos Queiroz,; Antônio Dionísio Feitosa Noronha Filho, (Acta Scientiae Veterinariae, 2023)
Background: Omphalophlebitis is characterized as an omphalopathy that affects the umbilical vein. In these cases, ultrasonography can help identify the severity of abdominal lesions and guide the choice of treatment. Marsupialization of the umbilical vein is a surgical procedure indicated in cases where this vessel presents with purulent secretion up to the liver parenchyma. This report describes a case of omphalophlebitis in a heifer treated by marsupialization of the umbilical vein. The preoperative and postoperative sonographic findings are also described. Case: A 4-day-old Holstein calf was attended at the Veterinary Hospital (HV) of the Universidade Federal de Goiás (UFG), Goiânia, Brazil. On physical examination, the animal was found to be apathetic, with tachycardia, tachypnea, hyperthermia, hyperemic mucous membranes, and moderate dehydration. An increase in volume was observed in the umbilical region, with local hyperthermia, firm consistency, and sensitivity to palpation. On deep palpation of the abdomen, a mass originating in the umbilical region and extending cranially was observed, leading to the suspicion of omphalophlebitis. Abdominal ultrasonography revealed external umbilical abscess and omphalophlebitis. Initially, conservative treatment with antibacterial and anti-inflammatory drugs was performed; however, there was no improvement in the clinical picture. Therefore, exploratory celiotomy was performed to remove the umbilical infectious focus. During the procedure, it was verified that the umbilical vein was dilated with a thickened wall until its insertion in the hepatic parenchyma, hence removal of the infected region through a ligature was not possible. Thus, marsupialization of the umbilical vein was performed to create a cutaneous opening for drainage of the purulent contents. In the postoperative period, antibacterial, anti-inflammatory, and analgesic drugs were administered. Dressing of the surgical wound and of the umbilical vein lumen was performed with topical polyvidone at 0.2%. Removal of the stitches was done 14 days postoperatively. Weekly ultrasonographic examinations were performed, which showed a gradual reduction in the diameter of the umbilical vein throughout the postoperative period. Thirty days after the surgical procedure, no further drainage of the purulent content was observed from the umbilical vein, and healing of the stump was demonstrated. After 7 months, a repeat ultrasonography was performed, revealing normal echogenicity and echotexture of the hepatic parenchyma and complete atrophy of the umbilical vein. Discussion: Umbilical vein marsupialization is a surgery rarely described in the literature, and no report has followed the evolution of a case by ultrasonography. The ultrasound examination of the umbilical structures was essential for the definitive diagnosis and choice of surgical treatment. Marsupialization of the umbilical vein was chosen due to the impossibility of ligature of this vessel, which presented with thickened walls and lumen filled with purulent content until its insertion into the liver. Postoperative monitoring via serial ultrasonography examinations allowed follow up of the evolution of the case and animal recovery. At the sonographic reevaluation after 7 months, the findings were unremarkable, indicating complete recovery of the patient. Umbilical marsupialization is a surgical technique that allows complete recovery of calves with severe omphalophlebitis. Ultrasonography is fundamental for the diagnosis of omphalophlebitis and in determining the best therapeutic protocol. Sonographic evaluation during the postoperative period allows follow-up of the progression of lesions in abdominal structures and helps in defining the prognosis. Keywords: omphalophlebitis, ultrasonography, hepatic abscess, liver, surgery. Título: Onfaloflebite em bezerra - tratmento com marsupialização da veia umbilical Descritores: onfaloflebite, ultrassonografia, abscesso hepático, fígado, cirurgia.